种渣油延迟焦化过程中收率实时预测方法 (2019)
本发明公开了种渣油延迟焦化过程中收率实时预测方法。该方法结合延迟焦化反应器特点，建立轴向绝热反应器的数学模型。基于物料平衡、热量平衡原理对收集的装置实时数据进行处理，结合智能优化算法，对延迟焦化反应动力学参数进行实时校正，使机理模型能够精确描述装置实际运行情况。在精确机理模型基础上，分析关键操作/工艺条件，对延迟焦化产品收率的影响，结合神经网络建模技术，将操作条件与收率数据之间进行关联，建立收率代理模型，提高收率数据计算速度。根据收率影响趋势进行分段线性化，求解线性方程，获得PIMS计划模型中相应的Delta-Base收率数据，实现延迟焦化装置收率实时预测，为建立精确的计划优化PIMS模型提供理论支撑。 The invention discloses a yield real-time prediction method in the residual oil delayed coking process. The method combines features of a delayed coking reactor, and a mathematical model of an adiabatic reactor in the axial direction is established. Based on the material balance principle and the thermal balance principle, processing is conducted on collected device real-time data, an intelligent optimization algorithm is combined, real-time correction is conducted on delayed coking reaction kinetic parameters, and a mechanism model can accurately describe device actual operation conditions. Based on the accurate mechanism model, the influence of key operation and technological conditions on the yield of dela